Selection of elite genotypes of Indian mustard (Brassica juncea L.) through AMMI, GGE biplot and MTSI: Selection of elite genotypes of Indian mustard (Brassica juncea L.) through AMMI, GGE biplot and MTSI - SURENDRA KUMAR; RAHUL BHARDWAJ; ARCHNA RAI; VIKAS KHANDELWAL; RUMIT PATEL; RAMESH; S J JHAMBHULKAR; MANISH KUMAR (Journal of Oilseeds Research, 2023)
Forty-five Indian mustard genotypes were evaluated under four environments. Significant G × E interaction leads to stability analysis using AMMI, GGE biplot and MTSI. GGE biplot identified G43 as a vertex genotype in E1 and E2; G41 in E3 and E4 for seed yield and G16 in E1 and E2; G11 in E3 and G13 in E4 for oil content. AEC illustrated that G27 and G30 were most stable for seed yield and G14 for oil content. Environment, E1 and E4 were more discriminating whereas E1 and E3 were more representative for seed yield and oil content, respectively. MTSI identified promising genotype G42, G43, G45, G40, G41 and G44. According to AMMI, E1 and E2 were potential whereas E3 and E4 were poor environment. Genotypes G39, G2, G18 and G6 for seed yield whereas G45 and G9 for oil content were broadly adapted to all environments.